2017
DOI: 10.1021/acs.jmedchem.7b00397
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Structure-Based Design and Parallel Chemistry to Identify a Potent, Selective, and Brain Penetrant Phosphodiesterase 2A Inhibitor

Abstract: Phosphodiesterase 2A (PDE2A) inhibitors have been reported to demonstrate in vivo activity in preclinical models of cognition. To more fully explore the biology of PDE2A inhibition, we sought to identify potent PDE2A inhibitors with improved brain penetration as compared to current literature compounds. Applying estimated human dose calculations while simultaneously leveraging synthetically enabled chemistry and structure-based drug design has resulted in a highly potent, selective, brain penetrant compound 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Additional behavioral experiments using the MK-801-induced memory deficit mouse model revealed that the PDE2 inhibitor is able to reverse the MK-801-induced local field potential disruption. This study represents another evidence of the potential use of selective PDE2A inhibitors in treating neurological and neuropsychiatric disorders [101].…”
Section: Phosphodiesterase 2 Inhibitorsmentioning
confidence: 72%
See 1 more Smart Citation
“…Additional behavioral experiments using the MK-801-induced memory deficit mouse model revealed that the PDE2 inhibitor is able to reverse the MK-801-induced local field potential disruption. This study represents another evidence of the potential use of selective PDE2A inhibitors in treating neurological and neuropsychiatric disorders [101].…”
Section: Phosphodiesterase 2 Inhibitorsmentioning
confidence: 72%
“…Two PDE2 inhibitors sharing the same chemical scaffold were developed by Pfizer, PF-05085727 and PF-05180999 (also called PF-999) [100,101]. PF-05085727 showed an IC 50 of 2.0 nM and selectivity of up to 4000-fold over other PDEs was identified by Pfizer as well [101]. PF-05085727 increased the level of cGMP in rodent brain regions expressing the highest levels of the PDE2A enzyme.…”
Section: Phosphodiesterase 2 Inhibitorsmentioning
confidence: 99%
“…When compared to reactions with alcohols, the use of more nucleophilic amines and thiols led to significantly more tele-substituted products (Entries 1-6, 12-17 and 21-26). This trend may explain why tele-substituted isomers were apparently not seen in the literature synthesis of related structures 23 in which the incoming nucleophile was restricted to alcohols.…”
Section: Resultsmentioning
confidence: 95%
“…The resulting intermediate (20) expels chloride, leading to the ipso-substituted product (21). On the other hand, a plausible mechanism for the tele-substitution reaction could involve the initial attack of the nucleophile at the 8-position (22, Figure 3B), followed by loss of the 8-position proton as part of the elimination of the chloride (23). Since mechanistic studies on tele-substitution reactions are scarce in the literature, we sought better understanding of the process operating in this case.…”
Section: Resultsmentioning
confidence: 99%
“…The p -trifluorophenyl group of 1 occupies a pocket distinct to PDE2 and necessary for selectivity over other PDEs. 15 The additional methyl group on the pyrazole ring of 1 , relative to 3 , reduced the strain energy to adopt the bound conformation by enforcing a local minimum structure with a dihedral angle (pyrazole–imidazotriazinone) of ∼45°. This conformation requires less than 1 kcal/mol to adopt the bound conformation dihedral angle of ∼66°, mimicking the low-energy conformation of 3 (dihedral angle of 67°), optimal for the interaction of the p -trifluorophenyl group with the selectivity pocket.…”
mentioning
confidence: 99%